Role of MRI in Treatment Planning of Endometrial CA - Gulati, Parveen; Agarwal, Ankita; Gulati, Vaibhav (Indographics, 2022)
Purpose Endometrial carcinoma is a major cause of morbidity and mortality in women. It is the fourth most common cancer in women and its incidence is rising. Clinical examination and endometrial sampling form the mainstay of diagnosis. Magnetic resonance imaging (MRI) due to its superb soft tissue contrast can play an important role in the management of the disease. The present article reviews the role of MRI to exclude mimics, confirm the diagnosis, stage the disease, and in the follow-up of a patient with carcinoma of the endometrium.Method Using online databases including PubMed and Medline, literature was reviewed to assess the role of MRI to confirm the diagnosis, stage the disease, and follow-up in a patient of carcinoma endometrium. The examples published were taken from a personal file of cases.Results MRI with newer sequences like dynamic contrast studies and diffusion-weighted imaging can play an important role in excluding mimics, staging, and in the follow-up of the patient.Conclusion MRI with advanced sequences is the imaging modality of choice in pre- and postoperative evaluation of patients with endometrial carcinoma. It is the most sensitive imaging modality to evaluate myometrial invasion and early involvement of the cervix.
Keywords: endometrial CA; myometrium; MRI